Scıence, Technology, And Innovatıon: A Panacea For Small And Medıum-Sızed Busınesses Sustaınabılıty In South Afrıca - Mmaphale Kgahliso Maoto Mmaphale Kgahliso Maoto (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Due to the recent transition of moving from a brick-and-mortar type of business to an online business by Small and Medium-sized Businesses (SMBs), Covid 19 was seen as a major driver of this transition worldwide. The majority of SMBs find themselves vulnerable and lost in the middle of Science, Technology, and Innovation (STI) implementation. The advanced virtual reality (E-business) of running a business should be given a high priority to ensure that the SMB owners concerning STI are well trained and uplifted. This skill is needed for the betterment of their businesses. STI has been given a lot of attention in the education sector and the business arena has less or no attention specifically in South Africa. A lack of resources, e-skills, and fear of collaborating with big businesses encourages the researcher to conduct this study. This article endeavours to review the literature on the merging of STI as a strategy to enhance SMBs in South Africa. The review’s focus is on books, peer-reviewed articles, and conference papers between the years 2014 and 2023. Furthermore, this article will conclude by recommending that the collaboration between various business stakeholders and government, particularly, the Department of Science and Technology be encouraged to empower SMBs.